Screening and Identification of Nitrogen-Fixing Bacteria from Rhizosphere of Mangrove Jenu Tuban - Salsabila, Syarifah; Rahmawati, Hanif Nur; Fatimah, Fatimah (Journal of Bio-Molecule Research and Engineering, 2022)
this study aims to determine nitrogen-fixing bacteria isolates from Jenu mangrove soil, their macroscopic and microscopic characteristics, and species based on the 16S rRNA gene. nitrogen-fixing bacteria were filtered qualitatively using a selective nitrogen-free bromothymol (NFB) medium. screening results showed that six bacterial isolates from Jenu Tuban mangrove soil had potential as nitrogen -fixing bacteria, namely 1,8,10,15, and 16. the six nitrogen-fixing bacteria had varied microscopic characteristics and were gram-positive. based on the identification of the 16S rRNA, it was found that the six isolates were detected as a Bacillus cereus group with 99% query cover and 99.58% identitiy; Bacillus toyonensis with 99% query cover and 99.79% identity; Bacillus altitudinis with 99% query cover and 99.72% identity; Bacillus megaterium with 99% query cover and 99.79% identity; and Bacillus aerius with 98% query cover and 99.86% identitiy.